SAM II and lidar aerosol profile comparisons during AASE - Osborn, M. T.; Poole, L. R.; Wang, Pi-Huan (1990)
The NASA Langley Research Center aerosol lidar system was one of several instruments that flew aboard a DC-8 during the Airborne Arctic Stratospheric Expedition. Several of the Stratospheric Aerosol Measurement II (SAM II) altitude profiles of aerosol extinction were close enough in time and space to allow for intercomparison with the lidar measurements of aerosol backscatter. Comparisons between three SAM II 1.0 micron aerosol extinction profiles and analogous profiles inferred from nearly simultaneous airborne lidar measurements are discussed. The other two comparisons show the first near-simultaneous SAM II/lidar measurements of a polar stratospheric cloud (PSC). The comparison made well within the edge of a relatively homogeneous PSC layer was also good, especially using an extinction-to-backscatter model derived from in situ PSC particle size measurements.